Inkjet Printed Circuits with 2D Semiconductor Inks for High‐Performance Electronics. (13th May 2021) - Carey, Tian; Arbab, Adrees; Anzi, Luca; Bristow, Helen; Hui, Fei; Bohm, Sivasambu; Wyatt‐Moon, Gwenhivir; Flewitt, Andrew; Wadsworth, Andrew; Gasparini, Nicola; Kim, Jong M.; Lanza, Mario; et al.
Abstract: Air‐stable semiconducting inks suitable for complementary logic are key to create low‐power printed integrated circuits (ICs). High‐performance printable electronic inks with 2D materials have the potential to enable the next generation of high performance low‐cost printed digital electronics. Here, the authors demonstrate air‐stable, low voltage (<5 V) operation of inkjet‐printed n‐type molybdenum disulfide (MoS2 ), and p‐type indacenodithiophene‐ co ‐benzothiadiazole (IDT‐BT) field‐effect transistors (FETs), estimating an average switching time of τMoS2 ≈ 4.1 μs for the MoS2 FETs. They achieve this by engineering high‐quality MoS2 and air‐stable IDT‐BT inks suitable for inkjet‐printing complementary pairs of n‐type MoS2 and p‐type IDT‐BT FETs. They then integrate MoS2 and IDT‐BT FETs to realize inkjet‐printed complementary logic inverters with a voltage gain | A v | ≈ 4 when in resistive load configuration and | A v | ≈ 1.4 in complementary configuration. These results represent a key enabling step towards ubiquitous long‐term stable, low‐cost printed digital ICs. Abstract : The authors demonstrate air‐stable, inkjet‐printed n‐type molybdenum disulfide (MoS2 ) and p‐type indacenodithiophene‐co‐benzothiadiazole (IDT‐BT) field‐effect transistors (FETs) with a mobility >0.1 cm 2 V −1 s −1 and an I on / I off ratio of ≈ 10 3 . The integrated FETs enable inkjet‐printed logic inverters operating at low voltage with a voltage gain | A v | ≈ 4 and microsecond switching times. This represents a fundamental step towards enabling low‐cost printed and stable integrated circuits.